Divergência genética entre tipos morfológicos de mandacaru (Cereus sp.; Cactaceae) propagados na natureza e regenerados in vitro - Eloi, Ivone Batista de Oliveira (2014)
The genetic relationship was evaluated at molecular level between Mandacaru somaclones with atypical morphology (monstrous or monstruosus), regenerated from the calus culture of Cereus peruvianus and Mandacaru plants with monstrous phenotype (C. peruvianus var. monstruosus or C. monstruosus) disseminated in nature. Amplified Fragments Length Polymorphism (AFLP) technique was employed in 51 samples of Mandacaru disseminated in nature and regenerated in vitro, with different stalk morphologies. Six AFLP primers combinations were used, producing 534 fragments of which 503 (94.19%) were polymorphs and revealed mean polymorphism within morphotypes at 74.98% and mean genetic diversity (h) of 0.2722. Genetic divergence (GST) between the samples of the five morphotypes of the mandacaru stalks was high (GST = 0.1957). Similarity relationships between the mandacaru samples (disseminated in nature and by somaclones) proved them to be of the same species (genetic identity rates between 0.8747 and 0.9456) and that the different morphological types may be considered varieties of the species C. peruvianus. At the molecular level, the nomenclature C. peruvianus var. monstruosus is more proper than C. monstruosus. Analysis of the manner the morphological types of mandacaru are genetically structured showed that somaclones monstruosus produced in the calus culture are genetically divergent, at the molecular levels, of plants of the variety C. peruvianus monstruosus disseminated in nature.